Understanding and implementing play as a learning pedagogy: Narratives of practitioners in early childhood mobile units - Zukiswa Nhase; Mmakgabo Angelinah Selepe; Chinedu Ifedu Okeke (Journal of Childhood, Education & Society)
This research examined practitioners' narratives on understanding play as a learning pedagogy in early childhood mobile units. The national curriculum framework encourages practitioners and teachers in early childhood settings to employ a variety of play pedagogies to stimulate young learners to develop core skills in early childhood learning environments. Underpinned by Vygotsky's sociocultural theory, the article draws from the zone of proximal development and social interaction as significant theoretical concepts to examine practitioners’ understanding of play as a learning pedagogy in early childhood mobile units. A phenomenological within the qualitative research domain was utilised to gather in-depth data on the topic under investigation. The data was collected through semi-structured interviews with twenty practitioners purposively selected to provide their narratives on understanding play as a learning pedagogy in early childhood mobile units. The Atlas.ti software was used to analyse the collected data using a narrative strategy. The findings revealed that the practitioners maintained a high standard of service delivery within the mobile Early Childhood Care and Education unit contexts, which was transformative, high-quality and play-based. This paper contributes to the existing knowledge of delivering high-quality play-based learning pedagogy in early childhood settings.